Performance analysis on location update cost of multihoming-based scheme in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abdul Latif, Suhaimi; Mohd. Ramli, Huda Adibah; Hasan, Mohammad Kamrul (Institute of Electrical and Electronics Engineers Inc., 2014)
The protocol which is considered as a most widespread Mobility Management Protocol (MMP) is entitled as Network Mobility Basic Support Protocol (NEMO BSP). The foremost function of NEMO BSP is to maintain the ongoing Internet connectivity at the time of handoff among different access networks through establishing a tunnel among Mobile Router (MR) and its Home Agent (HA). Nevertheless, NEMO BSP inherits several shortcomings namely higher handoff latency and packet loss. This causes performance destruction for the real time scenarios (i.e. video streaming) seriatim on Mobile Network Nodes (MNNs) and fails to ensure seamless handover in mobile networks. This effect is predominantly significant in wireless environment. Accordingly, it can preserve seamless handoff by using a number of interfaces in NEMO. In this paper, a basic synopsis on mobility management in multihomed networks is given in a combined manner. Likewise, it evaluates Location Update Cost (LUC) by qualitative analysis to expose that multihoming-based scheme possess minor cost than NEMO BSP